Iot Based Power Loom Monitoring System - Shah Awais, Shahzad Mobeen, Ashfaque Ahmed, Siddiqui Ahmed Mohsin, Fahad Bilal (International Journal of Advanced Science and Technology, 2020)
Textile industry is that the one among the most important industry after agriculture. The demand of the assembly is increasing day by day thanks to increase within the population. Loom is one the foremost important tool within the industrialization of waving. Internet of things in industry bring the new revolution called Industrial Internet of Things (industry 4.0) that deals with the Efficiency, Safety and Security of the machines in manufacturing plants. This paper provides monitoring and alert of various parameter of loom by using onto temperature sensor, humidity sensor, current transformer, rotary encoder and proximity sensor. The Arduino Uno board is employed as a brain of the system during this paper. The system will hook up with the web network through ESP8266 Wi-Fi module. The info collected from the sensor is going to be published to cloud-based backend systems for added processing and analysis. Because the data are going to be offered on public/private cloud are often right to use by anywhere anytime. Smart monitoring system delivers us the well solution to flee unexpected damages within the different a part of the machine. This technique mainly targets to gather several data like the quantity of fabric woven, temperature of the motor, humidity, mechanical vibration, speed of motor and weft and warp defects.Keywords: IOT, Power Loom, Arduino Uno, ESP8622, sensor, industry 4.0